A reliable and intelligent protocol for distributed data mining architecture in sporadic wireless sensor network - Wagan, A.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Distributed Data Mining (DDM) approaches are considered most suitable for managing large datasets. DDM can reduce the communication cost, computational cost, and storage cost. However a key issue for DDM is accuracy of knowledge discovery. To mitigate the accuracy issue, it is necessary to provide reliable network. In practice, it is assumed that the network is available all the time but in reality, it may not available most of the time. In this study, we considered a sporadic wireless sensor network (SWSN), SWSN is a wireless network where most of the time a complete path is not available from a source to a destination, or such a path is highly unreliable. It is also possible in this type of network a communication path is available for a very short time and it may breaks when try to send data over it and limited storage capacity. The objective of this study is to overcome the above mentioned issues by providing a reliable and intelligent protocols for DDM architecture in a SWSN. Â© 2015 IEEE.